2020
DOI: 10.1007/s11128-019-2565-2
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude estimation without phase estimation

Abstract: This paper focuses on the quantum amplitude estimation algorithm, which is a core subroutine in quantum computation for various applications. The conventional approach for amplitude estimation is to use the phase estimation algorithm, which consists of many controlled amplification operations followed by a quantum Fourier transform. However, the whole procedure is hard to implement with current and near-term quantum computers. In this paper, we propose a quantum amplitude estimation algorithm without the use o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
298
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(301 citation statements)
references
References 27 publications
3
298
0
Order By: Relevance
“…However, research to improve the algorithms is ongoing [52][53][54]. Here we have used a new algorithm [22] that retains the AE speed-up but that uses less gates to measure the price of an option. Furthermore, we employed a simple error mitigation scheme that allowed us to greatly reduce the errors from the noisy quantum hardware.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, research to improve the algorithms is ongoing [52][53][54]. Here we have used a new algorithm [22] that retains the AE speed-up but that uses less gates to measure the price of an option. Furthermore, we employed a simple error mitigation scheme that allowed us to greatly reduce the errors from the noisy quantum hardware.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the required number of qubits and the resulting circuit depth, Suzuki et al have shown that AE can be performed without requiring quantum phase estimation while still maintaining a quadratic speed-up [22]. To this extent, they exploit that…”
Section: Amplitude Estimationmentioning
confidence: 99%
See 3 more Smart Citations